Retraction Note: LncRNA TUG1 was upregulated in osteoporosis and regulates the proliferation and apoptosis of osteoclasts - Ye Han; Chunying Liu; Ming Lei; Shaosong Sun; Wenkui Zheng; Yanan Niu; Xi Xia (Journal of Orthopaedic Surgery and Research, 2020)
This article has been retracted. Please see the Retraction Notice for more detail: 10.1186/s13018-020-02000-1 .